Fit for Industry 4.0 Innovative Learning and Tea ching for Digitalization and Automation (Volume 60) - Spöttl, Georg; Paryono, Paryono; Parvikam, Siriporn (wbv Media, 2021)
This volume presents a further training concept on Industry 4.0 for vocational teachers, which was developed for transnational use by the "Gesellschaft für Internationale Zusammenarbeit" (GIZ) together with SEAMEO VOCTECH (Regional Centre for Vocational and Technical Education and Training) and ASEAN (Association of Southeast Asian Nations) for transnational use. In connection with the thematic focus on digitalisation and the accompanying change in the world of work, innovative teaching and learning methods for self-reliant learning and the promotion of communicative and social competences are presented. In the transfer project, the professional and didactical competences of teachers and trainers are promoted.